Green, yellow or black? Genetic differentiation and adaptation signatures in a highly migratory marine turtle. Issue 1954 (14th July 2021) - Álvarez-Varas, Rocío; Rojas-Hernández, Noemi; Heidemeyer, Maike; Riginos, Cynthia; Benítez, Hugo A.; Araya-Donoso, Raúl; Reséndiz, Eduardo; Lara-Uc, Mónica; Godoy, Daniel A.; Muñoz-Pérez, Juan Pablo; Alarcón-Ruales, Daniela E.; Alfaro-Shigueto, Joanna; et al.
Abstract : Marine species may exhibit genetic structure accompanied by phenotypic differentiation related to adaptation despite their high mobility. Two shape-based morphotypes have been identified for the green turtle ( Chelonia mydas ) in the Pacific Ocean: the south-central/western or yellow turtle and north-central/eastern or black turtle. The genetic differentiation between these morphotypes and the adaptation of the black turtle to environmentally contrasting conditions of the eastern Pacific region has remained a mystery for decades. Here we addressed both questions using a reduced-representation genome approach (Dartseq; 9473 neutral SNPs) and identifying candidate outlier loci (67 outlier SNPs) of biological relevance between shape-based morphotypes from eight Pacific foraging grounds ( n = 158). Our results support genetic divergence between morphotypes, probably arising from strong natal homing behaviour. Genes and enriched biological functions linked to thermoregulation, hypoxia, melanism, morphogenesis, osmoregulation, diet and reproduction were found to be outliers for differentiation, providing evidence for adaptation of C. mydas to the eastern Pacific region and suggesting independent evolutionary trajectories of the shape-based morphotypes. Our findings support the evolutionary distinctness of the enigmatic black turtle and contribute to the adaptive research and conservation genomics of a long-lived and highly mobile vertebrate.